The association of listed family firms and listed government related companies with the firms' performances in Malaysia / Nursyafika Hj Mohd Yusoff - Hj Mohd Yusoff, Nursyafika (2013)
The objective of this study is to examine the association of listed family firm (LFF) and listed government related companies (LGRCs) and the firms' performance. The sample includes 495 companies listed on Bursa Malaysia for the year 2012. Multiple regression has been employed to test the hypotheses. Nine control variables included in this study which are the board size, board composition, role duality, firm size, firm age, debt ratio, firm growth, auditor type (Big 4) and financial expertise. The finding of this study indicates that listed family firms have correlation with firms' performance. A finding has revealed that the listed family firms perform better than LGRCs. The bigger the firm size, the higher the firm's performance as measured with Tobin's Q. The results also show that, the role duality is extremely significant positive associated with the Tobin's Q. This suggests that when there is a presence of role duality, it will contribute to higher firm performance. However, the finding for listed government related companies (LGRCs) show that there is no correlation between LGRCs and firms' performance.